Case Volume-Dependent Changes in Operative Morbidity following Free Flap Breast Reconstruction: A 15-Year Single-Center Analysis. Issue 3 (September 2021) - Ochoa, Oscar; Pisano, Steven; Ledoux, Peter; Nastala, Chet; Arishita, Gary; Garza, Ramon; Ketchum, Norma; Song, Xuemei; Michalek, Joel; Chrysopoulo, Minas
Abstract : Background: Operative morbidity is a common yet modifiable feature of complex surgical procedures. With increasing case volume, improvement in morbidity has been reported through designated procedural processes and greater repetition. Defined as a volume-outcome association, improvement in breast reconstruction morbidity with increasing free flap volume requires further characterization. Methods: A retrospective analysis was conducted among consecutive free flap patients using a two-microsurgeon model between January of 2002 and December of 2017. Patient demographics and operative characteristics were obtained from medical records. Complications including unplanned surgical intervention (take-back) and flap loss were obtained from prospectively kept databases. Individual surgeon operative volume was estimated by considering overall practice volume and correcting for the number of surgeons at any given time. Results: During the study period, 3949 patients met inclusion criteria. A total of 6607 breasts underwent reconstruction with 6675 free flaps. Mean patient age was 50 ± 9.4 years and mean body mass index was 28.8 ± 5.0 kg/m 2 . Bilateral reconstruction was performed on 2633 patients (66.5 percent), with 4626 breasts (70.5 percent) reconstructed in the immediate setting. Overall, breast and donor-site complications were reported in 507 breasts (7.7 percent) and 607 cases (15.4 percent), respectively. Take-back was required in 375 cases (9.5 percent), with complete flap loss occurring in 57 cases (0.9 percent). Based on annual flaps per surgeon, the incidence of complications decreased with increasing volume (slope = −0.12; p = 0.056). Conclusion: Through procedural efficiency and execution of defined clinical processes using a two-microsurgeon model, increases in microsurgical breast reconstruction case volume result in decreased morbidity. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.